Student’s scientific argumentation skills in biology: A gender-based analysis - Nisak, Hoirun; Antika, Linda Tri (STKIP Persada Khatulistiwa Sintang, 2024)
Scientific argumentation skill is important to develop in learning because it empowers students' way of thinking in forming new knowledge, stimulates activity, learns to solve problems, build socio-cultural activities through presentations and criticism, encourages students to express their thoughts, understand concepts more easily and get used to critical thinking and logical. This research aimed to determine the significance of differences between scientific argumentation skills based on gender. Research data was obtained from sample class data, namely class XI Science at Bustanul Mubtadiin Proppo Pamekasan High School with 22 students. Measurement of scientific argumentation skills based on gender using an essay writing test with a scientific argumentation rubric using the Osborne Argument Model. Aspects measured were based on the quality of rebuttal, data, collateral, support, refutation, or presence of conflicting claims. The hypothesis test used was an independent sample T-Test using the Jamovi Statistics program. This study reported that the scientific argumentation skills of male and female students were significantly different, which scientific argumentation skills of female students were higher than males. This research provided implications for students to be skilled in scientific argumentation, especially in biology.